Efek Kombinasi Doxorubicin dan Ekstrak Daun Pepaya (Carica papaya L.) terhadap Sel Payudara Pada Tikus Sprague Dawley yang Diinduksi DMBA (7,12-Dimethilbenzene(a)ntrazena) - Fatma Zuhrotun Nisa; Mary Astuti; Sofia Mubarika Haryana; Agnes Murdiat (JURNAL NUTRISIA, 2016)
Background: treatment of cancer is currently done by biopsy and chemotherapy. Chemotherapy is a cancer treatment that is costly and toxic effect conferring on normal cells. Objective: to know the effect of combination chemotherapy with Doxorubicin as agents of papaya leaf extract as an agent against chemo preventive breast cells on rat Sprague Dawley DMBA induced. Method: this research is experimental research with design post test only with control group. This research uses 60 rats which are divided into 6 groups of placebo groups, groups, groups of DMBA, Doxorubicin, papaya leaf extract groups, group 1 combination (Doxorubicin 50 50 Papaya leaf extract) and group 2 combination (Doxorubicin 25 75 papaya leaf extract). Research time during the 120 days that consists of the first 3 weeks of treatment were given continued grant of DMBA during 5 weeks (twice a week) and continued treatment back to 6 weeks. The analysis was conducted for three times at the end of week 8, the end of the week to 12 and the end of the week to 16. Any analysis will be carried out the killing mice by as much as 3 tails per group. Parameters measured is histopathology breast tissue and breast cancer cell proliferation. Results: the breast tissue histopathology observations indicate that treatment combination I have the ability to prevent the occurrence of breast cancer and also improve the breast cells underwent karsinogenesis. Conclusion: the results of staining method with IHC (Immunohistochemistry) Ki-67 shows that treat the combination I have the lowest level of proliferation than the treatment and the combination of papaya leaf extract II. Keyword: papaya leaves, cancer, breast, Doxorubicin